Movilidad, activismo cultural e identidad Amazónica en y desde el extranjero (2010-2023) - Castillo Torres, Daniel Enrique (2024)
This research project describes the life stories of five indigenous Shipibo people from the Amazon who have traveled for long periods abroad or decided to stay and live there. The research describes how they have redefined their identities after the experience of mobility and having developed some cultural activities in and from Germany, Austria, France and Argentina, all within the framework of globalization. This knowledge is important because it fills gaps in the current history of migration of Amazonian peoples and explains a new phenomenon related to identity, migration and transnational culture. The research methodology starts from ethnographic principles, as it implements techniques such as observation, construction of life histories, audiovisual recording and serial and semi-structured interviews that have been conducted since 2018 and continued until the end of 2023. The objectives of the project is to discuss indigenous identity in these contexts. And the results show that identity is an agential process independent of the cultural or political structure of the "indigenous", it is pragmatic and economic for these cases studied.